Correlation of Leg Muscle Explosive Power with Sickle Kick Performance in Pencak Silat Athletes - Hadisan, Hadisan; Nursyait, Sultan Mappalinrung; Firmansyah, M. Deni; Azhari, Tini Sri; Yuliana, Yuliana (Indonesian Journal of Sport Management, 2024)
Background: Pencak silat is a martial art that requires a combination of technique, strength, speed, and agility. One of the main attack techniques in pencak silat is the crescent kick, which requires explosive leg muscle ability so that the kick can be done quickly, powerfully, and precisely. Methods: This study uses a quantitative research method with a correlational design. The population in this study was 30 students. Sampling in this study used a total sampling technique. The sample in this study amounted to 30 students. The instrument to measure the explosive power of the leg muscles was the standing broad jump test, the instrument to measure the ability of the crescent kick was the ability test of the crescent kick for 10 seconds. The data analysis technique uses descriptive statistics, analysis prerequisite tests with normality tests, linearity, and using hypothesis tests with correlation tests with the help of SPSS version 23. Results: based on the results of the data analysis, the calculated r value is 0.776 and the significance level value is 0.000 <0.05 with a coefficient of determination of 0.603 or 60.3%, which means there is a significant relationship between the explosive power of the leg muscles and the ability of the sickle kick. Conclusion: This study shows that there is a significant relationship between the explosive power of the leg muscles and the performance of the sickle kick in pencak silat athletes. The higher the explosive power of the leg muscles owned by the athlete, the better the strength, speed, and accuracy of the resulting sickle kick. Thus, the explosive power of the leg muscles is an important physical factor that directly influences the performance of the sickle kick technique in pencak silat. Implications and Recommendations: the results of this study imply that the explosive power of the leg muscles plays an important role in improving the performance of the sickle kick in pencak silat athletes.